2001
DOI: 10.1038/35098027
|View full text |Cite
|
Sign up to set email alerts
|

A sperm ion channel required for sperm motility and male fertility

Abstract: Calcium and cyclic nucleotides have crucial roles in mammalian fertilization, but the molecules comprising the Ca2+-permeation pathway in sperm motility are poorly understood. Here we describe a putative sperm cation channel, CatSper, whose amino-acid sequence most closely resembles a single, six-transmembrane-spanning repeat of the voltage-dependent Ca2+-channel four-repeat structure. CatSper is located specifically in the principal piece of the sperm tail. Targeted disruption of the gene results in male ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
1,000
1
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 830 publications
(1,074 citation statements)
references
References 20 publications
(17 reference statements)
37
1,000
1
10
Order By: Relevance
“…One future line of research could investigate if other proteins such as CatSper [99,100] and/or other ion transporters form signaling complexes in SU sperm, where they reside and how they function in the cell. sAC, AC2 and AC9 are distributed along SU sperm.…”
Section: Discussionmentioning
confidence: 99%
“…One future line of research could investigate if other proteins such as CatSper [99,100] and/or other ion transporters form signaling complexes in SU sperm, where they reside and how they function in the cell. sAC, AC2 and AC9 are distributed along SU sperm.…”
Section: Discussionmentioning
confidence: 99%
“…However, genetic ablation studies suggested that these candidate proteins were not functionally necessary for male fertility or some compensatory mechanism for their loss may be present [64][65][66][67][68]. The molecular identity of the first sperm specific ion channel required for male fertility in mice was determined in 2001 with the cloning of CatSper1 [24]. The first member of the CatSper family of genes, CatSper1 is the pore forming ␣ subunit of the Cation channel of Sperm (CatSper).…”
Section: Calcium Channels and Hyperactivationmentioning
confidence: 99%
“…Reverse transcription-polymerase chain reactions (RT-PCR) for the synthesis of complementary DNA (cDNA), 12 μL aliquots of master mixture containing 100 ng of human testes RNA, 1 μL of 500 ng/μL oligo(dT) [12][13][14][15][16][17][18] primer (Invetrogen, Grand Island, NY, USA), and 9 μL of diethylpyrocarbonate-treated water were heated to 70°C for 10 min and put on ice. RT reactions were performed in 20 μL containing master mixture, 4 μL of 5X first-strand synthesis buffer, 0.1 M dithiothreitol, 10 mM of each dNTP, and 200 units of Superscript TM II RNase H -reverse transcriptase (Invetrogen, Grand Island, NY, USA).…”
Section: Reverse Transcriptionmentioning
confidence: 99%
“…Sperm express various voltage-gated Ca 2+ channels [13,14]. Certain voltagegated Ca 2+ channels have been shown to be critical for sperm motility by knockout experiments in mice [15,16]. In addition to the cAMP-dependent PK-A pathways and Ca 2+ signaling pathways, other signaling pathways are also likely to play roles.…”
Section: Introductionmentioning
confidence: 99%